Human rights : new dimensions and challenges : manual on human rights - Symonides, Janusz; Unesco (Aldershot [England] ; Brookfield, VT : Ashgate, 1998)
Human Rights: New Dimensions and Challenges has been prepared by UNESCO with the aim of creating an international teaching aid for institutions of higher education. The book presents the interrelation and interdependence between human rights, and peace, democracy, development and the environment. It analyses obstacles and threats to human rights at the dawn of the twenty-first century and suggests ways and means to overcome them.
1. New Human Rights Dimensions, Obstacles and Challenges: Introductory Remarks / Janusz Symonides -- Pt. I. New Dimensions. 2. Human Rights and Peace / Vojin Dimitrijevic. 3. Democracy and Human Rights: Civil, Political, Economic, Social and Cultural / David Beetham. 4. The Development of the Right to Development / Upendra Baxi. 5. Human Rights and the Environment / Antonio Augusto Cancado Trindade -- Pt. II. Obstacles. 6. Human Rights and Extreme Poverty / Louis-Edmond Pettiti and Patrice Meyer-Bisch. 7. Discrimination, Xenophobia and Racism / Rudiger Wolfrum. 8. Human Rights and Tolerance / Claudio Zanghi. 9. Terrorism and Human Rights / Colin Warbrick -- Pt. III. Challenges. 10. Human Rights and Scientific and Technological Progress / C. G. Weeramantry. 11. Globalization and Human Rights / Virginia A. Leary. 12. Education for Human Rights / Vitit Muntarbhorn.
Includes bibliographies and index
Keywords: Human rights -- Study and teaching